Toxicity and metabolism of acephate in adult and larval insects - Hussain, M. A.; Mohamad, R. B.; Oloffs, P. C. (Taylor & Francis, 1984)
Adult and larval insects from the terrestrial and aquatic environments were exposed to acephate. The chemical was more toxic to adult insects than to larvae, and was a poor insect cholinesterase inhibitor in vitro compared to methamidophos which was a much stronger inhibitor. Both acephate and methamidophos inhibited the adult cholinesterase in vitro much more strongly than they did the larval enzymes. Acephate was metabolized by the insects to methamidophos which did not appear to be the only metabolite, although no other metabolites were looked for. The cholinesterase of insects exposed to sublethal levels of acephate was inhibited, but this inhibition appeared to be due to the combined effect of acephate and methamidophos and not to any hypothetical substance with greater anticholinesterase activity. This was bourne out when acephate was incubated with mixed function oxidases (MFO). No activated product with potent anticholinesterase activity was identified. Methamidophos was not produced by the MFO system but by some other unidentified mechanism.